A derivation of factors influencing homeopaths to promote quackery in Sindh - Khan, Rehan (Journal of the Pakistan Medical Association, 2023)
This article provides multifaceted information as well as an assessment of how and why homoeopaths engage in quackery, which is neither safe, effective, or legal. The purpose of this study was to investigate the factors that influence the majority of homeopaths in Sindh to promote quackery through allopathic medical system, which is outside the boundaries of a homeopath’s practice license and competency. The study also explains why homeopathy has remained popular in Sindh, Pakistan, despite its limitations and waning popularity in the United States (USA), the United Kingdom (UK), Russia, Australia, Canada, France, Germany, Switzerland, and Spain over the last decade, based on major national clinical research studies claiming that homeopathic medicines are no more effective than a placebo. Keywords: Homeopathy, Quackery prone homeopaths, Aiding & abetting quackery.